Construção de um painel interativo para o ensino de genética com os alunos da modalidade EJA - Educação de Jovens e Adultos - Galvão, Thais de Araújo (2020)
In view of the need for improvements on Basic Education, in the modality of youth and adults education, and intending to use methodologies with the greatest involvement of students, this academic research deals with the elaboration of a didactic model that seeks to assist students in such modality on the teaching and learning process, bringing the theory of genetics teaching closer to their worldview. This research was developed in six stages, the first and second being carried out through an expository and conversational class. The third stage consisted of the application of a questionnaire, from which the students' understanding of the topic addressed was assessed. In the fourth and fifth stages, the interactive panel (didactic model) was made and contextualized. In the sixth and final stage, the previously answered questionnaire was reapplied with changes, in order to assess the before and after of the use of the didactic model. The making of the interactive panel was an efficient way of systematization, important for the maturation of previously worked concepts, because the motivation, the interaction with colleagues and the challenge in the act of assembling led students to understand the approached concepts in a pleasant way, making thus effective the learning process in an opposite way to the traditional method.